Application of Plackett-Burman design for screening of parameters for the production of tetrathionate hydrolase by Thiobacillus ferrooxidans - Othman, Emeliana; Yusof, Faridah; Azmi, Azlin Suhaida (Taylor's University, 2015)
Enzymatic devulcanisation is one of the methods of recycling waste rubber tire. Among all devulcanised methods that are introduced, biological method is a safer choice because it does not include any harmful or toxic chemicals, and is normally not energy intensive. The process deems more efficient and less expensive compared to various other devulcanisation methods. This method was done by exposing a surface of a vulcanised rubber piece to at least one enzyme, secreted from chemolithoautotrophic iron- and sulphur-oxidising bacterium to break the sulphur bonds in the vulcanised rubber structure, rendering it more acceptable to be recycled. By applying the enzymatic devulcanisation, it is hoped that the amount of demand of raw rubber can be reduced and at the same time helps to reduce the solid waste disposal problem. In this study, the process parameters that affect the tetrathionate hydrolase activity secreted from Thiobacillus ferrooxidans was screened using PlackettBurman design (PBD). Among the various variables, results showed initial pH, agitation rate, temperature of incubation, inoculum size and calcium chloride concentration were determined as the most influential variables on tetrathionate hydrolase production.